Flesh, Foil, and Authenticity: Reflections on Johann AR Roduit’s “Flesh and Foil” - Gunderson, Martin (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2017)
Johann AR Roduit’s poem, “Flesh and Foil,” raises a number of issues regarding enhancement, especially the need for principles to guide the process of human enhancement. The guidance that the poem seeks can be found in a combination of virtue ethics and authenticity.